Gastrointestinal tract colonization with Candida albicans and mucosal immune response in mice treated with Artemisinin and Fluconazole orally - SEENAA J. BADER; ATYAF S. HAMIED (Anais da Academia Brasileira de Ciências)
Abstract The results showed that after treating C. albicans with Artemisinin (0.104 mg/ml) for 3 hours the number of C. albicans decreased and affected the morphology hyphae and growth of Candida compared with Fluconazole (150 mg/ml) and control (infected mice). The biomarker levels in the tongue showed high levels of MDA and TGFβ (623±1.5pg/ml, 586.1±0.13pg/ml respectively) in (infected mice with fungi). IL-37 was recorded high level (49.21±0.21pg/ml) in (Neoral +Fungi + artemisinin + fluconazole) compared with negative control. The finding biomarker levels in stomach showed high levels of MDA and IL-37 (533.8±1.9, 69.76±0.39pg/ml) in (Neoral + Fungi + artemisinin + fluconazole) compared with control. TGF β was recorded high level (1002±0.32pg/ml) in (Neoral + Fungi + Artemisinin) compared with negative control. The biomarker levels in intestine showed high levels of MDA and TGFβ (1149±0.34pg/ml, 1089±0.3pg/ml respectively) in (mice infected with fungi). IL-37 was recorded high level (74.14±0.14pg/ml) in (Neoral + Fungi + artemisinin + fluconazole) compared with negative control (normal mice). The biomarker levels in serum showed high levels of MDA and TGFβ (1668±0.12 pg/ml, 1629±0.05 pg/ml respectively) in (mice infected with fungi) at (P<0.05). IL-37 was recorded high level (135.1±0.8pg/ml) in (negative control). In conclusion, artemisinin has a role as antifungal and C. albicans infection causes the imbalance in immunity.